Resveratrol Inhibits Cdk5 Activity through Regulation of p35 Expression. Issue 1 (7th July 2011) - Utreras, Elias; Terse, Anita; Keller, Jason; ladarola, Michael J; Kulkarni, Ashok B
Background: We have previously reported that cyclin-dependent kinase 5 (Cdk5) participates in the regulation of nociceptive signaling. Through activation of the ERK1/2 pathway, Tumor Necrosis Factor-α (TNF-α ) induces expression of Egr-1. This results in the sustained and robust expression of p35, a coactivator of Cdk5, in PC12 cells, thereby increasing Cdk5 kinase activity. The aim of our present study was to test whether resveratrol, a polyphenolic compound with known analgesic activity, can regulate Cdk5/p35 activity. Results: Here we used a cell-based assay in which a p35 promoter-luciferase construct was stably transfected in PC12 cells. Our studies demonstrate that resveratrol inhibits p35 promoter activity and also blocks the TNF-α mediated increase in Cdk5 activity in PC12 cells. Resveratrol also inhibits p35 expression and blocks the TNF-α mediated increase in Cdk5 activity in DRG neurons. In the presence of resveratrol, the MEK inhibitor decreased p35 promoter activity, whereas the inhibitors of p38 MAPK, JNK and NF- κ B increased p35 promoter activity, indicating that these pathways regulate p35 expression differently. The TNF-α -mediated increase in Egr-1 expression was decreased by resveratrol treatment with a concomitant reduction in p35 expression and protein levels, resulting in reduced Cdk5 kinase activity. Conclusions: We demonstrate here that resveratrol regulates p35 promoter activity in PC12 cells and DRG neurons. Most importantly, resveratrol blocks the TNF-α -mediated increase in p35 promoter activity, thereby reducing p35 expression and subsequent Cdk5 kinase activity. This new molecular mechanism adds to the known analgesic effects of resveratrol and confirms the need for identifying new analgesics based on their ability to inhibit Cdk5 activity for effective treatment of pain.